2022
DOI: 10.3389/fneur.2022.811062
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Calprotectin Is Predictive for Short-Term Functional Outcomes of Acute Ischemic Stroke

Abstract: BackgroundBlood-based prognostic biomarkers of acute ischemic stroke (AIS) are limiting. Calprotectin is suggested to be involved in directing post-stroke inflammatory conditions. However, the pathological alteration of circulating calprotectin in AIS is yet to be thoroughly elucidated. Therefore, this study aimed to investigate the levels and clinical relevance of calprotectin in AIS.MethodsThis study recruited 271 patients with AIS within 24 h since symptom onset and 145 non-stroke healthy controls (HC) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Our study design of calprotectin dynamics reveals an association with IS outcome after the T4 time point (median 110 h). This finding exhibits a modest deviation from prior research, which assessed calprotectin levels solely at a single time point during the earlier stages of the disease [18][19][20]. The Chinese multicenter prospective study among 4785 patients with IS from two independent cohorts measured calprotectin concentrations, showing that baseline concentrations (within 72 h) were independently associated with increased risks of adverse clinical outcomes at 3 months following IS [18].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Our study design of calprotectin dynamics reveals an association with IS outcome after the T4 time point (median 110 h). This finding exhibits a modest deviation from prior research, which assessed calprotectin levels solely at a single time point during the earlier stages of the disease [18][19][20]. The Chinese multicenter prospective study among 4785 patients with IS from two independent cohorts measured calprotectin concentrations, showing that baseline concentrations (within 72 h) were independently associated with increased risks of adverse clinical outcomes at 3 months following IS [18].…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the study observed significantly higher calprotectin concentrations in patients with a poor prognosis compared to those with a good prognosis. Furthermore, the study demonstrated an independent relationship between baseline calprotectin levels within 24 h and the progression of IS disease during a 2-week follow-up interval [19]. In a Spanish study, higher calprotectin levels were associated with 3-month mortality, hemorrhagic transformation, and lower 3-month functional independence in 748 patients sampled within the first 24 h after IS onset [20].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, higher protein levels proved to be an effective predictor of unfavorable short-term prognosis. 44 The biological behavior of plasma S100B protein and S100A1 protein seems to be quite similar, and there is substantial structural and sequence commonality. 15 Evidence from previous studies on S100B protein also showed analogous findings to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Como se desarrolla en el capítulo 2, la calprotectina mostró una importante asociación con la mortalidad en nuestra cohorte mejorando los modelos predictivos que incluían los marcadores pronósticos tradicionales. Este marcador, poco conocido en enfermedades cerebrovasculares pero de uso común en enfermedad inflamatoria intestinal y enfermedades reumatológicas, destaca por su estabilidad y fácil medición que ha propiciado su extensión al campo de las enfermedades cerebrovasculares, tanto en hemorragia subaracnoidea 298 como en ictus 299,300 . La calprotectina liberada por neutrófilos ha demostrado interaccionar con las plaquetas y modificar la reactividad de las mismas favoreciendo condiciones de tromboinflamación en procesos como el infarto de miocardio 29 y su presencia en el trombo es otro marcador más de la interacción plaqueta-leucocito en el proceso de trombosis.…”
Section: Tromboinflamación Y Pronósticounclassified